Linkage of biopsy, cancer, and population records aimed at the estimation of family risks in neoplasia: a pilot study. Issue 2 (June 1991) - Barrai, I; Nenci, I; Guidi, E; Dell'Acqua, G; Formica, G; Barbujani, G; Marzola, A; Marani, G; Barale, R; Beretta, M
Abstract : STUDY OBJECTIVE--The aim was to link individual demographic and medical records into sibships to obtain the sibling distribution of biopsies and cancers, and thereby calculate heritability and recurrence risks in families, thus aiding early diagnosis and prevention of cancers. DESIGN--The 157, 823 individual records of the inhabitants of the town of Ferrara in Italy were automatically linked into 106, 821 sibships. A 10% sample (10, 842 sibships) was then extracted from the distribution of sibships and tabulated, for linkage to medical records. PATIENTS--The biopsy records at the Institute of Pathological Anatomy of the University of Ferrara were manually linked to cancer records and then to sibships. It was possible to construct the distribution of 2062 biopsies and of 829 cancers in sibships. RESULTS--From the distribution of biopsies and tumours in sibships, it was possible to estimate the incidence of tumours in the population (0.052) and in siblings of affected (0.083), and to apply to such distributions current methods for the estimate of heritability (h2 = 0.246) and of recurrence risks of tumours in sibships, age independent. CONCLUSIONS--The study shows that the procedure resulting in the estimation of incidences and recurrence risks for tumours could be completely automated, and extended to whole populations and homogeneous subgroups in post industrial cultures.